One-Pot Synthesis of N-Monosubstituted Ureas from Nitriles via Tiemann Rearrangement - Wang, Chien-Hong; Hsieh, Tsung-Han; Lin, Chia-Chi; Yeh, Wen-Hsiung; Lin, Chih-An; Chien, Tun-Cheng (Synlett, 2015)
Amidoximes, obtained from the reaction of nitriles with hydroxylamine, underwent Tiemann rearrangement in the presence of benzenesulfonyl chlorides (TsCl or o-NsCl) to form the N-substituted cyanamides. Subsequently, acidic hydrolysis of the cyanamides afforded the corresponding N-monosubstituted ureas. The synthesis of N-monosubstituted ureas from nitriles was accomplished by three steps in one pot, which provides a direct access to versatile N-monosubstituted urea derivatives from a wide variety of nitriles.
Keywords: urea; cyanamide; amidoxime; hydrolysis; Tiemann rearrangement